Дослідження впливу технологічних режимів ламінування та лакування на якість продукції - Зацерковна, Р. С.; Слоцька, Л. С. (ТОВ «Видавництво Ліра-К», 2025)
The work is devoted to the study of the finishing of cardboard packaging by varnishing and lamination. The lamination process modes were studied: temperature and speed. The properties of varnished prints were studied. Cause-and-effect diagrams were constructed to assess the influence of factors on the quality of lamination and varnishing in the manufacture of packaging.
Keywords: ламінування; лакування